2021
DOI: 10.3390/ma14247542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waterjet Machining Parameters on the Cut Quality of PP and PVC-U Materials Coated with Polyurethane and Acrylate Coatings

Abstract: The article focuses on the machining of polymeric materials polypropylene (PP) and un-plasticized poly vinyl chloride (PVC-U) after surface treatment with polyurethane and acrylate coatings using waterjet technology. Two types of waterjet technologies, abrasive waterjet (AWJ) and waterjet without abrasive (WJ), were used. The kerf width and its taper angle, at the inlet and outlet of the waterjet from the workpiece, were evaluated. Significant differences between AWJ and WJ technology were found. WJ technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…When using conventional methods [ 19 , 20 , 21 , 22 ] of dividing materials with different coatings and surface treatments, they can be damaged, for example, by delamination, especially due to the contact of the tool with the workpiece. Research has shown that it is appropriate to use an unconventional machining method using water jet technology [ 20 , 23 , 24 ] characterized by considerable flexibility of adjustable machining parameters. However, it is necessary to take into account the optimization of the cutting process for a specific application.…”
Section: Methodsmentioning
confidence: 99%
“…When using conventional methods [ 19 , 20 , 21 , 22 ] of dividing materials with different coatings and surface treatments, they can be damaged, for example, by delamination, especially due to the contact of the tool with the workpiece. Research has shown that it is appropriate to use an unconventional machining method using water jet technology [ 20 , 23 , 24 ] characterized by considerable flexibility of adjustable machining parameters. However, it is necessary to take into account the optimization of the cutting process for a specific application.…”
Section: Methodsmentioning
confidence: 99%
“…However, these cutting methods are not suitable for CIPP specimen preparation. The water jet cutting method will leave the nonuniform cutting gap and significant burrs [6], which will significantly affect the result of the bending test and tensile test due to the change of the cross-section area. Besides, water jet cutting machines usually require a large set-up space, which is not friendly to small businesses.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly crucial for precision cutting applications [11]. Additionally, in many cases, especially for rough machining, waterjet cutting eliminates the need for additional operations such as milling, resulting in time and cost savings [12]. Consequently, waterjet cutting has gained popularity as a surface treatment technology, surpassing other cutting methods, such as laser cutting and plasma cutting [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in many cases, especially for rough machining, waterjet cutting eliminates the need for additional operations such as milling, resulting in time and cost savings [12]. Consequently, waterjet cutting has gained popularity as a surface treatment technology, surpassing other cutting methods, such as laser cutting and plasma cutting [12,13]. Various researchers have employed both vibration and acoustic emission for the real-time monitoring of the AWJ (abrasive waterjet) process [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation